Pengaruh Literasi Digital, Review Produk, dan Rating Toko dalam Belanja Online Mahasiswa untuk Mendapatkan Barang yang Sesuai - Inabah, Licha; Pradikto, Sugeng (Journal of Science and Education Research, 2025)
Online shopping has become a major activity among college students, driven by ease of access, product variety, and time flexibility. However, the challenge of getting goods that meet needs and expectations still often occurs. This study aims to examine the role of digital literacy, product reviews, and store ratings in helping college students make the right purchasing decisions. Digital literacy is able to improve students' ability to search for, understand, and evaluate relevant information on online shopping platforms. Meanwhile, product reviews and store ratings are important references for building trust in the quality of goods and seller credibility. This study uses a quantitative approach with a questionnaire distribution method to students. Data were analyzed using regression techniques to determine the relationship between these variables. The results showed that digital literacy has a significant effect on students' ability to filter false or partial information, while product reviews and store ratings make an important contribution to increasing shopping trust and satisfaction. This study highlights the importance of broader digital literacy education among college students to improve a safe and effective online shopping experience, as well as the need for e-commerce platforms to provide transparent and accurate information.